Evaluasi Status Kesuburan Tanah pada Subak di Kecamatan Denpasar Selatan Berbasis Sistem Informasi Geografis - DEWI, NI WAYAN KRISTINA MONIKA; ARTHAGAMA, I DEWA MADE; TRIGUNASIH, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Evaluation of Soil Fertility Status in Subak in South Denpasar District Based on Geographic Information System Soil fertility is the ability of the soil to provide nutrients needed by plants to support their growth and reproduction, fertile soil conditions have water, air and nutrients in a fairly balanced state and are available according to plant needs, both physical, chemical and biological soil. This study aims to determine the fertility status of subak soil, the limiting factors of soil fertility status and provide direction for managing soil fertility in subak in South Denpasar District. This research was conducted using survey methods and soil test methods. Determination of soil chemical properties is matched with the criteria for assessing soil chemical properties and determining soil fertility status includes the results of chemical properties by combining soil fertility parameters according to PPT (1995). The results of the evaluation of soil fertility status in Subak, South Denpasar District can be grouped into 2 fertility statuses, namely medium and high fertility. Subaks classified as having moderate fertility status are Subak Sanur and Subak Sesetan. Meanwhile, subaks classified as having high fertility status are West Intaran Subak, East Intaran Subak, Renon Subak, Sidakarya Subak, Panjer Subak, Kerdung Subak, Kepaon Subak and Cuculan Subak. The limiting factor that makes the soil fertility status moderate in the study area is due to the low P-Total. The recommended management alternative is the addition of P fertilizer and the addition of organic matter so that soil fertility can be well maintained.